Ultraproductos de f-anillos proyectables - Guier, Jorge I. (1999)
In [7], Keimel representes the projectable f-rings as continuous sections of Hausdorff sheaves of totally ordered rings. Here, we give a result about the representation of ultraporducts of projectable f-rings in terms of the representation spaces  and the stalks of its factors.